Communication—Identifying and Managing Reversible Capacity Losses that Falsify Cycle Ageing Tests of Lithium-Ion Cells. Issue 13 (15th October 2020) - Burrell, Robert; Zulke, Alana; Keil, Peter; Hoster, Harry
Abstract : We report on a cycle ageing study of commercial NCA/Gr+Si cells, in which reversible capacity fluctuations turn a central experimental finding upside down: an upper voltage limit of 4.1 V seems to cause faster degradation than going all the way to 4.2 V. The underlying effect is the reversible loss of lithium inventory into passive anode overhang areas. We demonstrate how the resulting artefact arises from a combination of slow transport processes and the related time periods spent in specific state-of-charge regions. We propose an alternative visualisation tool to identify and manage such artefacts, often neglected in typical ageing studies.